FRI0724-HPR THE EFFECTIVENESS OF TAI CHI CHUAN IN OSTEOARTHRITIS OF THE KNEE: A SYSTEMATIC REVIEW. (June 2019) - Tai, Kevin; Batista de Souza, Ingred Merllin; Marques, Amelia Pasqual
Abstract : Background: Osteoarthritis (OA) is the most prevalent joint disease in the elderly. The signs and symptoms are degeneration of joint surface, pain, stiffness, swelling and decrease in physical function. Knee OA is the most common joint disease and more prevalent among older adults. Tai Chi Chuan is a safe exercise modality of Chinese origin, which may be a potentially in reducing symptoms. Objectives: The aim of systematic review was to identify the effects of Tai Chi Chuan in the elderly with knee osteoarthritis. Methods: This systematic review was registered in Prospero (CRD42018098699). MEDLINE, EMBASE, PEDro, Cochrane, Scopus, Scielo, Lilacs and Web of Science, were screened between May 2008 to May 2018 in English, Spanish, Portuguese and Mandarin language. Randomized controlled trials (RCTs) comparing Tai Chi to control conditions were included. Two authors independently assessed risk of bias using the risk of bias tool recommended by Jadad index. Outcome measures included were pain, stiffness, muscular strength, functionality and quality of life. Results: In the search we founded 161 studies, MEDLINE (29), Pedro (58), Web of Science (17), Embase (29), Cochrane (6), Scopus (18), Manual search (4). Eight articles were included and seven showed the effectiveness of Tai Chi Chuan, being higher to the interventions of the control groups, consisting of self-care educational activities, or strengthening and endurance exercises of knee flexors and extensors. Only one study, that patients received a lower limb resistance training program, presented better results in pain, stiffness and physical function scores. Tai Chi Chuan was not associated with adverse events. Conclusion: Tai Chi Chuan was effective in improving pain, stiffness and physical function of sleep quality, in addition to increased speed and step length during gait, and strength gain of knee extensor muscles in elderly patients with knee OA. This systematic review found moderate evidence for short-term improvement of pain, physical function and stiffness in patients with knee AO. More high quality RCTs are urgently needed to confirm these results. References: [1] Michael Wortley, Songning Zhang, Maxime Paquette, Erin Byrd, Lucas Baumgartner, Gary Klipple, John Krusenklaus, Larry Brown. Effects of resistance and Tai Ji training on mobility and symptoms in knee osteoarthritis patients. Journal of Sport and Health Science. 2013; 2: 209- 214. [2] Zhu Q, Huang L, Wu X, Wang L, Zhang Y, Fang M, Liu Y.Effects of Tai Ji Quan training on gait kinematics in older Chinese women with knee osteoarthritis: A randomized controlled trial. Journal of Sport and Health Science. 2016; 5: 297-303. [3] Pereira MM, Oliveira RJ, Silva MAF, Souza LHR, Vianna LG. Effects of Tai Chi Chuan on knee extensor muscle strength and balance in elderly women. Rev Bras Fisioter. 2008; 12: 121-6. [4] Lü J1, Huang L1, Wu X1, Fu W1, Liu Y2. Effect of Tai Ji Quan training on self-reported sleep quality in elderly Chinese women with knee osteoarthritis: a randomized controlled trail. Sleep Med. 2017; 33:70-75. Acknowledgement: To all collaborators in the Laboratory of the Professor PhD Marques for your collaborative support in all process. Disclosure of Interests: None declared